Adamantammonium as a novel functional group for anion exchange membranes with excellent comprehensive performances. (10th March 2017) - Wang, Jinlei; Chen, Ying; Wei, Qi; Yang, Shanzhong; Fang, Huagao; Wei, Haibing; Ding, Yunsheng
Abstract: In the pursuit of alkali stable cation as functional group for anion exchange membranes (AEMs), a novel adamantammonium (AdA) cation, which replacing methyl group of conventional trimethylammonium by an adamantyl group, was synthesized and investigated. 1 H NMR spectroscopy was employed to quantify the extent of decomposition and the results showed that > 99% adamantammonium remaining after 7 days immersion in 2 M NaOH (in D2 O) at 80 °C. The AdA functionalized benzyl type poly(2, 6-dimethyl phenylene oxide) polyelectrolytes, PPO-AdAs, were further prepared and characterized the AEM properties. Not only the chemical durability of these new PPO-AdA membranes, interestingly, but the conductivity and dimensional stability (water uptake and in-plane swelling) are superior to the benzylmethylammonium-benchmark PPO-based AEM (PPO-TMA). With the similar IEC values, the water uptake of PPO-AdA-41 sample is much lower than PPO-TMA-28, however, the conductivity of the former (15.7 mS cm -1, chloride conductivity at 50 °C) is higher than the latter (13.3 mS cm -1 ). Overall, the results of this study offer a base-stable cation, adamantammonium, and the corresponding adamantammonium-based AEMs for fuel cell applications with the advantages of chemical stability, enhanced conductivity and excellent dimensional stability as well as facial functionalization technique. Graphical abstract: Highlights: A novel adamantammonium cation with high alkaline stability for AEM applications was reported. The benzyl type AEMs based on adamantammonium show improved alkaline durability than benzylmethylammonium-benchmark AEM. The membranes exhibit high ionic conductivity and excellent dimensional stability.